Effect of Spanwise Semicircular Groove on NACA 0012 Airfoil - Almusawi, Mahdi S.; Rishack, Qais A.; Al-fahham, Mohammed A. (Basrah Journal for Engineering Sciences, 2022)
The efficiency of an airfoil can be improved by adjusting its surface. CFD software was used to investigate a 2D airfoil with and without a spanwise semicircular groove on the upper surface. NACA0012 airfoils with and without grooves were analyzed using the k-ω turbulence model. The lift and drag coefficients were used to compared. To investigate the effect of groove location on airfoil efficiency, a groove was added in various locations and compared to a smooth airfoil. The flow velocity remained constant at 20 m/s at all angles of attack (AOA). According to this study, which used ANSYS software to simulate it numerically, the presence of a semicircular groove affects the aerodynamics of the airfoil, resulting in an improved efficiency coefficient of lift, which has risen by 2.25 percent, while the drag coefficient has decreased by 4.32 percent.